The Practice of Information Dissemination by Affiliated Local Television in Lampung in News Production (A Case Study of Delta TV Lampung) - Irwantoro; Noning Verawati; Hanindyalaila Pienrasmi (Cita konsultindo, 2025)
This study explores the practice of information distribution carried out by networked local television in Lampung, focusing on news production activities at Delta TV Lampung. The research aims to examine the collaboration patterns between Delta TV, other local television stations, and regional government institutions. Using a qualitative approach and case study method, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that Delta TV Lampung functions as a centralized production hub, managing the entire news production process from planning to distribution to its media partners and contracted government agencies. This collaboration model not only enhances operational efficiency but also addresses the challenges posed by limited resources in the digital broadcasting era. Through a streamlined production system, Delta TV Lampung has maintained its position as a credible and competitive local media outlet. Moreover, the partnership creates a mutually beneficial ecosystem: partner stations receive ready-to-air content, while Delta TV gains reputational value and production sustainability.